Next‐Generation Sequencing Library Preparation from FFPE Tissue Samples. Issue 1 (4th January 2016) - Wolf, Kathrin; O'Neil, Dominic; Schroeer, Stefanie; Fang, Nan
Abstract: Formalin‐fixed, paraffin‐embedded (FFPE) tissue samples represent an invaluable biobank for retrospective cancer research with molecular methods such as real‐time PCR and next‐generation sequencing (NGS). However, the usage of FFPE material in NGS approaches involves several challenges associated with the limited quantity and quality of DNA. This protocol describes how to purify DNA from FFPE material and how to prepare it for downstream NGS workflows including fragmentation, size selection, and library preparation for Illumina MiSeq/HiSeq sequencing. © 2016 by John Wiley & Sons, Inc.